2014
DOI: 10.1007/s00705-014-2268-z
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of homologous and heterologous interactions between viroplasm proteins P6 and P9-1 of the fijivirus southern rice black-streaked dwarf virus

Abstract: P6 of southern rice black-streaked dwarf virus (SRBSDV) is a multifunctional protein that is involved in the formation of viroplasms by interacting with P5-1. Here, we used yeast two-hybrid and bimolecular fluorescence complementation assays to show that there were homologous and heterologous interactions between SRBSDV P6 and P9-1 in yeast and plant cells. Mutational analysis showed that the N-terminal region (residues 1-93) of P6 was necessary for the interaction between P6 and P9-1. Self-interactions only o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 22 publications
1
14
0
Order By: Relevance
“…After COS processing, we identified some defense-related proteins, simultaneously the expression of SRBSDV P9-1 and P5 protein were down-regulated [42,43]. Previous studies have shown that the interaction between P9-1 and P5 were essential proteins that formed viroplasms [44,45]. Our results indicated that COS may decrease the infection ability of SRBSDV.…”
Section: Discussionmentioning
confidence: 85%
“…After COS processing, we identified some defense-related proteins, simultaneously the expression of SRBSDV P9-1 and P5 protein were down-regulated [42,43]. Previous studies have shown that the interaction between P9-1 and P5 were essential proteins that formed viroplasms [44,45]. Our results indicated that COS may decrease the infection ability of SRBSDV.…”
Section: Discussionmentioning
confidence: 85%
“…By immunogold labelling, P1 is found to be localized in the viroplasms and virion crystals, supporting the view that it functions as a structural protein (L. Xie, H. M. Zhang, unpublished data). P5‐1 and P9‐1 were detectable in the filamentous and granular matrix, indicating that both of them are components of viroplasms (Li et al ., , ; Mao et al ., ). P6 also participates in viroplasm formation by interacting with itself (Li et al ., ).…”
Section: Genome Structure and Functionmentioning
confidence: 99%
“…P6 also participates in viroplasm formation by interacting with itself (Li et al ., ). During the formation of viroplasms, P6 is thought to serve as a key regulator for recruiting P5‐1 and P9‐1 by protein interactions (Li et al ., , ). The terminal residue of P9‐1 plays an important role in the formation of viroplasms as shown by structural analysis (Li et al ., ).…”
Section: Genome Structure and Functionmentioning
confidence: 99%
“…These viroplasm matrix proteins can act as the targets for antiviral molecule screening (106). Other viral nonstructural and structural components are then recruited to viroplasm matrices for genome replication and progeny virion assembly (18,19,46,61,68,99,105). Currently, whether the insect components are involved in the formation of viroplasms is unknown.…”
Section: Viral Multiplicationmentioning
confidence: 99%